2014
DOI: 10.1002/14651858.cd008324.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapies versus antidepressant medication, alone and in combination for depression in children and adolescents

Abstract: Analysis 4.3. Comparison 4 Combination therapy versus psychological therapy plus placebo, Outcome 3 Remission by cutoff (post-intervention).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
0
8

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 148 publications
0
84
0
8
Order By: Relevance
“…Regarding the effectiveness of pharmacological, psychological, and combined treatment, there was limited evidence to conclude about the superiority of any treatment over another. 29 In respect to the effectiveness and safety of pharmacological treatment options for child and adolescent depression, the systematic review of the literature highlighted the high heterogeneity among available studies, but suggested that fluoxetine should be the treatment of choice if pharmacological treatment is considered. 30 The same authors also reviewed the available evidence on interventions for preventing relapse and recurrence of depression in children and adolescents,…”
Section: Treatmentmentioning
confidence: 99%
“…Regarding the effectiveness of pharmacological, psychological, and combined treatment, there was limited evidence to conclude about the superiority of any treatment over another. 29 In respect to the effectiveness and safety of pharmacological treatment options for child and adolescent depression, the systematic review of the literature highlighted the high heterogeneity among available studies, but suggested that fluoxetine should be the treatment of choice if pharmacological treatment is considered. 30 The same authors also reviewed the available evidence on interventions for preventing relapse and recurrence of depression in children and adolescents,…”
Section: Treatmentmentioning
confidence: 99%
“…Whereas in adolescence there are a significant number of RCTs of both pharmacological and psychological interventions [7,8,9], literature in younger children (12 and under) is starkly lacking. It is possible that antidepressant medication may have a different level of efficacy in younger children and medication is also less likely to be acceptable to families of younger children.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason to reconsider the DSM diagnosis of adolescent MDD is that, in general, psychiatric diagnoses are only meaningful when linked to evidence-based treatment and a Cochrane meta-analysis that included more than 1,300 participants concluded that: “there is very limited evidence upon which to base conclusions about the relative effectiveness of psychological interventions, antidepressant medication and a combination of these interventions in children and adolescents” (13). Importantly, this meta-analysis included individual studies that are often used to advocate for cognitive behavioural therapy (CBT) and antidepressant medication for treating adolescent depression, such as the Treatment for Adolescents with Depression Study (14), funded by the National Institute of Mental Health.…”
Section: Introductionmentioning
confidence: 99%
“…CBT is currently the most common psychological treatment for adolescent depression, but even though it is considered evidence-based in adult MDD, it has not shown reliable longstanding effects in adolescents (13). It has been speculated that CBT, which was originally developed for adults, may not be as effective for adolescents with MDD due to differences in cognitive control (15) and reward sensitivity (16).…”
Section: Introductionmentioning
confidence: 99%